Goal-Setting Learning Principles: A Lesson From Practitioner - Zainudin bin Abu Bakar; Lee Mei Yun; NG Siew Keow; Tan Hui Li (Journal of Education and Learning (EduLearn), 2014)
One of the prominent theory was the goal-setting theory which was widely been used in educational setting. It is an approach than can enhance the teaching and learning activities in the classroom. This is a report paper about a simple study of the implementation of the goal-setting principle in the classroom. A clinical data of the teaching and learning session was then analysed to address several issues highlighted. It is found that the goal-setting principles if understood clearly by the teachers can enhance the teaching and learning activities. Failed to see the needs of the session will revoke the students learning interest. It is suggested that goal-setting learning principles could become a powerful aid for the teachers in the classroom.